Pengaruh Dukungan Keluarga dan Dukungan Sosial terhadap Kreativitas Siswa: Peran Mediasi Motivasi Intrinsik - Aini, Nabila Nida Nur; Aeni, Ida Nur (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to analyze the effect of family support and social support on students’ creativity with intrinsic motivation as a mediating variable.Method – This study uses a quantitative approach by distributing questionnaires containing research instruments developed based on each variable. The participants in this study consisted of 215 grade X students at MAN 02 Semarang City. The data analysis used is path analysis and sobel test. Data analysis was conducted to determine the direct and indirect effects between variables in the research model, and to test the significance of the role of the mediating variables involved. Findings – The results showed that family support has no effect on student's creativity (Asymp. Sig. value 0.126 > 0.05), which states that the higher or lower the family support felt by students does not affect the creativity of these students. There is a significant influence between social support and intrinsic motivation on student creativity with an Asymp. Sig. < 0.05. In addition, this study shows that the intrinsic motivation variable can fully mediate the effect of family support on student creativity and partially mediate the effect of social support on student creativity with the value of sig. < 0.05. Research Implications – The findings from this study indicate the importance of social support to enhance students' creativity, as well as the need for an environment that builds self-confidence. Intrinsic motivation is the link between family support and creativity, so families still play an important role in fostering student motivation, although it does not have a direct effect on creativity.